Repetitive transient paraplegia caused by painless acute aortic dissection. Issue 2 (19th February 2019) - Takeda, Shinsuke; Tanaka, Yoshihiro; Sawada, Yasuhiro; Tabuchi, Akihiko; Hirata, Hitoshi; Mizumoto, Toru
Abstract : Case: Making a precise diagnosis of type A acute aortic dissection (AAD) presenting with atypical symptoms might be challenging for clinicians. Misdiagnosis and misuse of thrombolytic therapy can have devastating consequences. Outcome: Herein, we report a case of painless type A AAD complicated by transient leg paresthesia, which was successfully treated with surgery. On admission, sudden onset of right leg numbness and muscle weakness was the only clue toward the correct final diagnosis. Conclusion: When patients present with vague neurological symptoms, physicians should not rule out the possibility of AAD until proven otherwise. Abstract : We report a case of painless acute aortic dissection complicated by transient leg paresthesia that was successfully treated with surgery.